THE MEDIATING ROLE OF CUSTOMER SATISFACTION ON REPURCHASE INTENTION: AN EVIDENCE FROMTHE SERVICE INDUSTRY - Kusumo, Maureen; Vidyanata, Deandra (Universitas Ciputra Surabaya, 2022)
This study aims to determine the effect of Service Quality on Repurchase Intentions with the mediation of Customer Satisfaction. This study is classified as quantitative research with a population of all start-up business’ consumers which engaged in the service industry. The sampling technique used in this study is purposive sampling with the criteria of consumers who have purchased Drip N' Dry services at least four times. The data in this study were collected by distributing questionnaires to 110 respondents. The results of this study indicate that Service Quality has no significant effect on Customer Satisfaction, Customer Satisfaction does not significantly affect Repurchase Intentions, but Service Quality has a significant positive effect on Drip N' Dry consumer repurchase intentions. Furthermore, the results of this study indicate that customer satisfaction does not mediate the effect of service quality on repurchase intention.